Association of Demographic and Lifestyle Factors with Semen Quality of Men with Fertility Problems Attending Infertility Center in North Karnataka - Makhadumsab M. Toragall; Sanat K. Satapathy; Girish G. Kadadevaru; Murigendra B. Hiremath (Indian Journal of Medical Specialities)
Background: Male factor is responsible for 50% of infertility cases. Universal deterioration in human sperm quality occurring in recent times is receiving a greater attention. The impact of numerous lifestyle factors including age, smoking, alcohol consumption, and exposure to occupational and environmental pollutants is unfavorable to male reproductive health. The present study intended to find out the association of demographic, occupational, and several lifestyle factors on semen quality of men diagnosed with infertility. Materials and Methods: The study enlisted 432 men diagnosed with fertility issue. Couples were administrated with a structured questionnaire to provide their demographic attributes and medical and reproductive health information. The collected data were statistically analyzed using SPSS software version 20.0. Results: The mean age of men was 34.44 ± 0.21 years at the time of consultation. Among seven semen abnormalities, asthenozoospermia was recorded the highest (30.09%). Most of the participants were having secondary education (32.26%), working as laborers (26.62%), and were having multiple addictions (27.77%). Decreased sperm count and motility was noticed among advanced age group and those with addictions. Different occupational statuses had substantial correlation with the sperm quality of participants. Conclusion: The incidence of male infertility and the potent lifestyle aspects studied have displayed an association with each other. However, influence of these aspects on impairment of male fertility can be overcome with modification toward healthier lifestyle.